Seismic Analysis of A 3 Dimensional High Rise Building Frame Considering Transfers Slab Using Analysis Tool Staad. Pro - Singhai, Karan Patel; Singhai, Ankita Singhai; Singhai, Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2024)
This study presented a seismic analysis of a high rise building with a transfer floor. Two structural models of high rise buildings were analyzed using static analysis method. For this seismic response of buildings such as bending moment and shear force were numerically evaluated. In this study, two different structural models of G+14 storey building had studied by providing a transfer slab at the bottom most storey of the building. The seismic response of high rise building such as storey shear, bending moment, displacement, axial force and torsion were numerically evaluated.